Changes in plasma metabolite concentrations and enzyme activities in aging riding horses - Asahi, Yukari; Arai, Toshiro; Tanaka, Yoshikazu (Frontiers in Veterinary Science, 2024)
In older horses, basal metabolic rate decreases and plasma metabolite and hormone concentrations related to energy metabolism change. The occurrence of age-related diseases, which increases in old animals, may enhance inflammatory reactivity (inflammaging). Finding appropriate treatment for inflammaging at the early stage may prevent various age-related diseases. Changes in metabolite and hormone concentrations, and enzyme activities involved in energy metabolism in the plasma of clinically healthy riding horses of various ages were measured to identify biomarkers of inflammaging (persistent low-grade inflammation that occurs with aging). All horses were clinically healthy, and their body condition scores (BCS) were 4 or 5 (9-point scale). Plasma triglyceride (TG), total cholesterol, blood urea nitrogen (BUN), insulin concentrations, malondialdehyde (MDA) and serum amyloid A (SAA) concentrations tended to increase with age. Adiponectin concentrations and plasma superoxide dismutase (SOD) and leukocytes AMPactivated protein kinase (AMPK) activities decreased, while plasma aspartate aminotransferase (AST), alanine aminotransferase (ALT) and glutathione peroxidase (GPx) remained unchanged as horses aged. Although riding horses that partake in continuous exercise seem to be less likely to develop inflammaging, horses over 17 years of age tended to show proinflammatory signs with disordered lipid metabolism. In riding horses, serum amyloid A, in combination with other markers, may be a useful biomarker for inflammaging and dysregulated lipid metabolism in aging horses.